Peran Humas Puskesmas Tanjung Morawa dalam Menyosialisasikan Penyebaran Stunting Melalui Media Sosial - Indriana, Loula Umaiyah; Saragih, M. Yoserizal; Abidin, Syahrul (Comit: Communication, Information and Technology Journal, 2024)
Stunting is a condition where a toddler experiences failure to develop due to acute nutritional deficiencies. Tanjung Morawa subdistrict is one of the subdistricts whose working area was designated as a stunting locus by the Deli Serdang regent. Limited publicity on stunting and the difficulty of approaching the public makes it difficult for public relations to maximize its role. This research aims to determine the role, obstacles and successes of Tanjung Morawa Community Health Center public relations in socializing the spread of stunting through journalistic media. The theories used are the theory of the four roles of public relations and the theory of communication barriers. The research method used is a descriptive method with a qualitative approach. Data collection techniques using interviews and observation. The results of the research show that the Public Relations Officer of the Tanjung Morawa Community Health Center has carried out all its roles well, although there is still one role which has been carried out less than optimally, namely as a communications technician. The biggest obstacle for public relations in carrying out its role is community behavior, while the success of public relations in carrying out its role is the freeing of 2 stunting locus areas which are the responsibility of and are under the auspices of the Tanjung Morawa Community Health Center.